Metabolic and Bariatric Surgery Utilization Trends in the United States: Evidence From 2012 to 2021 National Electronic Medical Records Network - Abdulrahman Alsuhibani, PharmD, MSc, PhD; Jonathan R. Thompson, MD, FACS, FASMBS; Patricia R. Wigle, PharmD, BCPS, BCACP, FCCP; Jeff Jianfei Guo, BPharm, PhD; Alex C. Lin, MS, PhD; Marepalli B. Rao, MS, PhD; Ana L. Hincapie, MS, PhD (Annals of Surgery Open)
Background:. Bariatric surgery has evolved over the past 2 decades yet assessing trends of bariatric surgery utilization in the growing eligible population is lacking. Aim:. This study aimed to update the trends in bariatric surgery utilization, changes in types of procedures performed, and the characteristics of patients who underwent bariatric surgery in the United States, using real-world data. Method:. This retrospective descriptive observational study was conducted using the TriNetX, a federated electronic medical records network from 2012 to 2021, for adult patients 18 years old or older who had bariatric surgery. Descriptive statistical analysis was conducted to assess patients’ demographics and characteristics. Annual secular trend analyses were conducted for the annual rate of bariatric surgery, and the specific procedural types and proportions of laparoscopic surgeries. Results:. A steady increase in the number of procedures performed in the United States over the first 6 years of the study, a plateau for the following 2 years, and then a decline in 2020 and 2021 (during the coronavirus disease 2019 pandemic). The annual rate of bariatric surgery was lowest in 2012 at 59.2 and highest in 2018 at 79.6 surgeries per 100,000 adults. During the study period, 96.2% to 98.8% of procedures performed annually were conducted laparoscopically as opposed to the open technique. Beginning in 2012, the Roux-en-Y gastric bypass (RYGB) procedure fell to represent only 17.1% of cases in 2018, along with a sharp decline in the adjustable gastric band (AGB) procedure, replaced by a sharp increase in the sleeve gastrectomy (SG) procedure to represent over 74% of cases in 2018. Conclusions:. Bariatric surgery utilization in the United States showed a moderate decline in the number of RYGB procedures, which was offset by a substantial increase in the number of SG procedures and a precipitous drop in the annual number of AGB procedures.